Communication: Reply to Fox and Schruben - Kleijnen, Jack P. C. (Management Science, 1978)
In the recent issue of Management Science Fox (Fox, B. 1978. Estimation and simulation. Management Sci. 24 (8, April) 860–861.) expressed doubts about the relevance of steady-state behavior. In a reply Schruben (Schruben, L. W. 1978. Reply to Fox. Management Sci. 24 (8, April) 862.) disagreed on this point. With Fox he was in favor of publishing failures of variance reduction techniques (VRT's). I would like to add the following remarks.